Safety of Digestive Endoscopy following Acute Coronary Syndrome: A Systematic Review - Alastair Dorreen; Sarvee Moosavi; Myriam Martel; Alan N. Barkun (Canadian Journal of Gastroenterology and Hepatology)
Background. The safety of endoscopy after an acute coronary syndrome (ACS) is poorly characterized. We thus performed a systematic review assessing the safety of endoscopy following ACS. Methods. Searches in EMBASE, Medline, and Web of Science identified articles for inclusion. Data abstraction was completed by two independent reviewers. Results. Fourteen retrospective studies yielded 1178 patients (mean 71.3 years, 59.0% male) having suffered an ACS before endoscopy. Patients underwent 1188 endoscopies primarily to investigate suspected gastrointestinal bleeding (81.2%). Overall, 810 EGDs (68.2%), 191 colonoscopies (16.1%), 100 sigmoidoscopies (8.4%), 64 PEGs (5.4%), and 22 ERCPs (1.9%) were performed 9.0±5.2 days after ACS, showing principally ulcer disease (25.1%; 95% CI 22.2–28.3%) and normal findings (22.9%; 95% CI 20.1–26.0%). Overall, 108 peri- and postprocedural complications occurred (9.1%; 95% CI 7.6–10.9%), with hypotension (24.1%; 95% CI 17.0–32.9%), arrhythmias (8.1%; 95% CI 4.5–18.1%), and repeat ACS (6.5%; 95% CI 3.1–12.8%) as the most frequent. All-cause mortality was 8.1% (95% CI 6.3–10.4%), with 4 deaths attributed to endoscopy (<24 hours after ACS, 3.7% of all complications; 95% CI 1.5–9.1%). Conclusion. A significant proportion of possibly endoscopy-related negative outcomes occur following ACS. Further studies are required to better characterize indications, patient selection, and appropriate timing of endoscopy in this cohort.